THE INFLUENCE OF LOCAL CULTURE ON NAMING OF FOOD AND DRINK IN ENGLISH: A CASE STUDY IN JIMBARAN VILLAGE, BADUNG REGENCY, BALI - Wayan Pastini; Putu Ayu Sudiparwati; Ni Kadek Eni Juniari; Isnan Waluyo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This article analyzes the practice of naming English menus in restaurants in Jimbaran Village, Badung Regency, Bali, particularly traditional Balinese dishes. Naming food requires consideration of the cultural associations embedded in the name, its meaning and function in the source language, and the translatability of the terms in the target language. Using a qualitative research approach and an ethnographic case study, this research will analyze how cultural values ​​are reflected in English menu names in Jimbaran Village. It will also examine how culturally based traditions dialogue with the modernity of globalization in menu naming. The results show that food and beverage naming in Jimbaran Village serves not only as a means of information for tourists but also as a strategy for representing local cultural identity. Many menu names combine English elements with local Balinese terms, either through literal translation or creative adaptation, to maintain authenticity while enhancing global appeal. This naming process reflects a negotiation between traditional values ​​and the modern demands of international tourism. Furthermore, it was found that the use of English on menus is often intended to build a professional image and be easily understood by tourists, while still maintaining traces of local culture through the insertion of typical terms such as grilled fish sauce Jimbaran, fish nyat-nyat, nasi goreng teba with sambal matah, sambal uleg, Bali coffee. Thus, the naming of menus in Jimbaran demonstrates the dynamics of language and cultural hybridization that emphasizes local identity in a global context.